Engineered macrophages as near-infrared light activated drug vectors for chemo-photodynamic therapy of primary and bone metastatic breast cancer - Huang, Yanjuan; Guan, Zilin; Dai, Xiuling; Shen, Yifeng; Wei, Qin; Ren, Lingling; Jiang, Jingwen; Xiao, Zhanghong; Jiang, Yali; Liu, Di; Huang, Zeqian; Xu, Xiaoyu; et al. (Nature communications, 2021)
Patients with primary and bone metastatic breast cancer have significantly reduced survival and life quality. Due to the poor drug delivery efficiency of anti-metastasis therapy and the limited response rate of immunotherapy for breast cancer, effective treatment remains a formidable challenge. In this work, engineered macrophages (Oxa(IV)@ZnPc@M) carrying nanomedicine containing oxaliplatin prodrug and photosensitizer are designed as near-infrared (NIR) light-activated drug vectors, aiming to achieve enhanced chemo/photo/immunotherapy of primary and bone metastatic tumors. Oxa(IV)@ZnPc@M exhibits an anti-tumor M1 phenotype polarization and can efficiently home to primary and bone metastatic tumors. Additionally, therapeutics inside Oxa(IV)@ZnPc@M undergo NIR triggered release, which can kill primary tumors via combined chemo-photodynamic therapy and induce immunogenic cell death simultaneously. Oxa(IV)@ZnPc@M combined with anti-PD-L1 can eliminate primary and bone metastatic tumors, activate tumor-specific antitumor immune response, and improve overall survival with limited systemic toxicity. Therefore, this all-in-one macrophage provides a treatment platform for effective therapy of primary and bone metastatic tumors. Bone metastases are associated with poor prognosis in patients with breast cancer and limited therapeutic options. Here the authors exploit near-infrared light responsive macrophages for the tumor-selective delivery of oxaliplatin prodrug for chemo-photodynamic therapy of primary and bone metastatic breast cancer.